Learning from the COVID-19 pandemic for future epidemics and pandemics preparedness and response in Guinea: Findings from a scoping review - Kolié, Delphin; Keita, Fatoumata Namaren; Delamou, Alexandre; Dossou, Jean-Paul; Van Damme, Wim; Agyepong, Irene Akua (Frontiers in Public Health, 2022)
The outbreak of the novel coronavirus (SARS-CoV-2) in December 2019 prompted a response from health systems of countries across the globe. The first case of COVID-19 in Guinea was notified on 12 March 2020; however, from January 2020 preparations at policy and implementation preparedness levels had already begun. This study aimed to assess the response triggered in Guinea between 27th January 2020 and 1st November 2021 and lessons for future pandemic preparedness and response. We conducted a scoping review using three main data sources: policy documents, research papers and media content. For each of these data sources, a specific search strategy was applied, respectively national websites, PubMed and the Factiva media database. A content analysis was conducted to assess the information found. We found that between January 2020 and November 2021, the response to the COVID-19 pandemic can be divided into five phases: (1) anticipation of the response, (2) a sudden boost of political actions with the implementation of strict restrictive measures, (3) alleviation of restrictive measures, (4) multiple epidemics period and (5) the COVID-19 variants phase, including the strengthening of vaccination activities. This study provides several learning points for countries with similar contexts including: (1) the necessity of setting up, in the pre-epidemic period, an epidemic governance framework that is articulated with the country's health system and epidemiological contexts; (2) the importance of mobilizing, during pre-epidemic period, emergency funds for a rapid health system response whenever epidemics hit; (3) each epidemic is a new experience as previous exposure to similar ones does not necessarily guarantee population and health system resilience; (4) epidemics generate social distress because of the restrictive measures they require for their control, but their excessive securitization is counterproductive. Finally, from a political point of view, decision-making for epidemic control is not always disinterested; it is sometimes rooted in political computations, and health system actors should learn to cope with it while, at the same time, safeguarding trusted and efficient health system responses. We conclude that health system actors anticipated the response to the COVID-19 pandemic and (re-) adapted response strategies as the pandemic evolved in the country. There is a need to rethink epidemics governance and funding mechanisms in Guinea to improve the health system response to epidemics.